2018
DOI: 10.1038/s41598-018-35023-0
|View full text |Cite
|
Sign up to set email alerts
|

Host Directed Therapy for Chronic Tuberculosis via Intrapulmonary Delivery of Aerosolized Peptide Inhibitors Targeting the IL-10-STAT3 Pathway

Abstract: Here we demonstrate that aerosols of host directed therapies [HDT] administered during a chronic Mycobacterium tuberculosis (Mtb) infection have bactericidal effect. The pulmonary bacterial load of C57BL/6 mice chronically infected with Mtb was reduced by 1.7 and 0.6 log10CFU after two weeks of treatment via aerosol delivery with ST3-H2A2, [a selective peptide inhibitor of the STAT3 N-terminal domain] or IL10R1-7 [selective peptide inhibitor for the IL-10Ra] respectively and when compared to control mice treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…IL-10 and TGFβ are reported to be conducive to Mtb survival due to their inhibitory effect on pro-inflammatory cytokine production and T cell activation (Othieno et al, 1999). Furthermore, IL-10 is reported to inhibit autophagy in Mtb-infected macrophages (Upadhyay et al, 2018). Infected THP-PKR macrophages also produced lower levels of IL-1β and TNFα compared to control macrophages (Figures 3E,F), two cytokines that are critical for host resistance to Mtb due to their pro-inflammatory effects and their role in activating macrophage cell death (Flynn et al, 1995;Keane et al, 1997;Mayer-Barber et al, 2010;Jayaraman et al, 2013).…”
Section: Pkr Expression Alters the Immunological Profile Of Macrophages During Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%
“…IL-10 and TGFβ are reported to be conducive to Mtb survival due to their inhibitory effect on pro-inflammatory cytokine production and T cell activation (Othieno et al, 1999). Furthermore, IL-10 is reported to inhibit autophagy in Mtb-infected macrophages (Upadhyay et al, 2018). Infected THP-PKR macrophages also produced lower levels of IL-1β and TNFα compared to control macrophages (Figures 3E,F), two cytokines that are critical for host resistance to Mtb due to their pro-inflammatory effects and their role in activating macrophage cell death (Flynn et al, 1995;Keane et al, 1997;Mayer-Barber et al, 2010;Jayaraman et al, 2013).…”
Section: Pkr Expression Alters the Immunological Profile Of Macrophages During Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%
“…Our Lm infection studies in mice with NK cell-intrinsic STAT3 deficiency showed that preventing STAT3 activation in this cell population has a protective effect. Similarly, inhibition of either STAT3 or IL-10Rα was recently shown to reduce lung burdens in a model of chronic infection with Mycobacterium tuberculosis (62). While this study did not address which cell types were essential for the observed therapeutic effects, the phenotype observed suggests STAT3-dependent IL-10 production similarly contributes to susceptibility in the context of this important pulmonary bacterial pathogen and demonstrate the potential for therapeutic targeting of STAT3/IL-10/IL-10R.…”
Section: Discussionmentioning
confidence: 98%
“…Given its detrimental role during Tb, IL-10 is an attractive target for HDT. An HDT approach applying aerosolized peptide inhibitors targeting the IL-10R alpha chain had major beneficial effects on Mtb control in C57BL/6 mice (73). Future studies need to elucidate whether such treatment could also be applicable in situations of coinfection-induced disease exacerbation.…”
Section: Discussionmentioning
confidence: 99%